1968
DOI: 10.1071/ar9680767
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sugar-cane mosaic virus and mosaic viruses of maize and Johnson grass in Australia

Abstract: Two isolates of maize dwarf mosaic virus originating from maize (MDMV(M)) and Johnson grass (MDMV(J)) were distantly related to an Australian and a Californian strain of sugar-cane mosaic virus (SMV). MDMV(M) was shown to be distantly related serologically to a Californian strain but not to an Ohio strain of MDMV; MDMV(J) was not shown to be related serologically to either the Californian or the Ohio strain of MDMV. MDMV(M), MDMV(J), and the Australian SMV produced similar symptoms on sweet corn (Zea mays var.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1970
1970
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A somewhat similar difference between BYMV (about 750 m~z) and pea mosaic virus (about 790-800 m~) was found by Taylor and Smith (1968), who nevertheless concluded that they were strains of one virus. A less pronounced difference in particle length between a sorghum isolate (784 m~x) and a surgarcane isolate (753 m~) of the sugarcane mosaic virus (yon Wechmar and Hahn, 1967) and between this virus (uneven length 650-750 m~) and maize dwarf mosaic virus (775 m~z) (Taylor and Pares, 1968) was also not considered to be sufficient to warrant the iselates concerned being regarded as different viruses. However, the great length and rigidity of PMV E 198 necessitates reconsideration of the identity of this pea mosaic virus isolate, and of the bearing of particle length on virus classification.…”
Section: Systemic or Local Infectionmentioning
confidence: 94%
“…A somewhat similar difference between BYMV (about 750 m~z) and pea mosaic virus (about 790-800 m~) was found by Taylor and Smith (1968), who nevertheless concluded that they were strains of one virus. A less pronounced difference in particle length between a sorghum isolate (784 m~x) and a surgarcane isolate (753 m~) of the sugarcane mosaic virus (yon Wechmar and Hahn, 1967) and between this virus (uneven length 650-750 m~) and maize dwarf mosaic virus (775 m~z) (Taylor and Pares, 1968) was also not considered to be sufficient to warrant the iselates concerned being regarded as different viruses. However, the great length and rigidity of PMV E 198 necessitates reconsideration of the identity of this pea mosaic virus isolate, and of the bearing of particle length on virus classification.…”
Section: Systemic or Local Infectionmentioning
confidence: 94%
“…Maize dwarf mosaic disease (MDMD) is one of the most common and devastating diseases affecting maize. Several RNA viruses, including Maize dwarf mosaic virus , Sugarcane mosaic virus (SCMV), Johnsongrass mosaic virus , Zea mosaic virus , Pennisetum mosaic virus and Sorghum mosaic virus can cause MDMD (Janson & Ellett, ; Williams & Alexander, ; Taylor & Pares, ; Shukla et al ., ; Seifers et al ., ; Fan et al ., ). All of these viruses belong to the genus Potyvirus , family Potyviridae (Hollings & Brunt, ; Adams et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…It occurs in many parts of the world where susceptible species are grown. A large number of SCMV strains have been reported from different parts of the world (3,5,16,17,22,23,24,29,32), and these were differentiated on the basis of host, reactions and serological tests. A large number of SCMV strains have been reported from different parts of the world (3,5,16,17,22,23,24,29,32), and these were differentiated on the basis of host, reactions and serological tests.…”
Section: Introductionmentioning
confidence: 99%